The King's speech [compact disc, unabridged] - Logue, Mark (Tantor Audio, 2011)
Albert, Duke of York began to see speech therapist Lionel Logue in a desperate bid to cure his lifelong stammer. Little did the two men know that this unlikely friendship would ultimately save the House of Windsor from collapse. The amiable Logue gave the shy young Duke the skills and the confidence to stand and deliver before a crowd. And when his elder brother, Edward VIII, abdicated the throne to marry for love, 'Bertie' was able to assume the reins of power as King George VI.